Mechanisms of formation of electron hole trap centers in LiKSO4 crystal - Nurakhmetov, T; Yussupbekova, B.N.; Zhangylyssov, K.B.; Sadykova, B.M.; Alibay, T.T.; Daurenbekov, D. H.; Kainarbay, A. Zh.; Zhunusbekov, A. M.; Zh. M. Salikhodzha, Zh. M. Salikhodzha; Tolekov, D.A. (Eurasian Journal of Physics and Functional Materials, 2026)
The mechanisms of creation of electron-hole trapping centers in LiKSO4 have been investigated by the methods of vacuum and thermal activation spectroscopy. It is shown that electron-hole trapping centers are formed during the trappingof electronsbyanionic complexes and localizationofa holein the lattice in the form of the radical SO. . The appearance of phosphorescence at 3.0-3.1 eV, 2.6-2.7 eV and 2.3-2.4 4 eV confirms the creation of electron-hole trap centers. Recommended Citation Nurakhmetov, T. N.; Salikhodzha, Zh. M.; Zhunusbekov, A. M.; Kainarbay, A. Zh.; Daurenbekov, D. H.; Alibay, T. T.; Sadykova, B. M.; Zhangylyssov, K. B.; Yussupbekova, B. N.; and Tolekov, D. A. (2021) "Mechanisms of formation of electron hole trap centers in LiKSO4 crystal," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 1, Article 3. DOI: https://doi.org/10.32523/ejpfm.2021050103